Summary of Informal Discussions with Central Bankers and Other Officials on Unconventional Monetary Policies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
A series of conference calls was held in March 2013 with selected representatives of central banks and other official agencies in advanced and emerging market economies to seek views on unconventional monetary policies (UMP). The key points raised during the discussions are summarized below. No views have been attributed to individual participants, and Fund staff is ultimately responsible for the contents of this summary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States